Atherosclerosis following renal injury is ameliorated by pioglitazone and losartan via macrophage phenotype. Issue 1 (September 2015) - Yamamoto, Suguru; Zhong, Jiayong; Yancey, Patricia G.; Zuo, Yiqin; Linton, MacRae F.; Fazio, Sergio; Yang, Haichun; Narita, Ichiei; Kon, Valentina
Abstract Objective Chronic kidney disease (CKD) amplifies atherosclerosis, which involves renin-angiotensin system (RAS) regulation of macrophages. RAS influences peroxisome proliferator-activated receptor-γ (PPARγ), a modulator of atherogenic functions of macrophages, however, little is known about its effects in CKD. We examined the impact of combined therapy with a PPARγ agonist and angiotensin receptor blocker on atherogenesis in a murine uninephrectomy model. Methods Apolipoprotein E knockout mice underwent uninephrectomy (UNx) and treatment with pioglitazone (UNx + Pio), losartan (UNx + Los), or both (UNx + Pio/Los) for 10 weeks. Extent and characteristics of atherosclerotic lesions and macrophage phenotypes were assessed; RAW264.7 and primary peritoneal mouse cells were used to examine pioglitazone and losartan effects on macrophage phenotype and inflammatory response. Results UNx significantly increased atherosclerosis. Pioglitazone and losartan each significantly reduced the atherosclerotic burden by 29.6% and 33.5%, respectively; although the benefit was dramatically augmented by combination treatment which lessened atherosclerosis by 55.7%. Assessment of plaques revealed significantly greater macrophage area in UNx + Pio/Los (80.7 ± 11.4% vs. 50.3 ± 4.2% in UNx + Pio and 57.2 ± 6.5% in UNx + Los) with more apoptotic cells. The expanded macrophage-rich lesions of UNx + Pio/Los had more alternatively activated, Ym-1 and arginine 1-positive M2 phenotypes (Ym-1: 33.6 ± 8.2%, p < 0.05 vs. 12.0 ± 1.1% in UNx; arginase 1: 27.8 ± 0.9%, p < 0.05 vs. 11.8 ± 1.3% in UNx). In vitro, pioglitazone alone and together with losartan was more effective than losartan alone in dampening lipopolysaccharide-induced cytokine production, suppressing M1 phenotypic change while enhancing M2 phenotypic change. Conclusion Combination of pioglitazone and losartan is more effective in reducing renal injury-induced atherosclerosis than either treatment alone. This benefit reflects mitigation in macrophage cytokine production, enhanced apoptosis, and a shift toward an anti-inflammatory phenotype.